Rwandan teacher training college’s mathematics teachers’ pedagogical content knowledge for teaching: assessment toward competency-based curriculum - Habiyaremye, Hashituky Telesphore; Ntivuguruzwa, Celestin; Ntawiha, Philothere (Frontiers in Education, 2023)
Teachers' knowledge and positive attitudes significantly impact educational settings. This study aimed to assess teachers mathematical knowledge for teaching (MKT) and their pedagogical content knowledge (PCK) attitudes. It was conducted among all 23 mathematics teachers from Rwandan teacher training colleges (TTCs). Employing a survey design, standardized performance and attitude tests were utilized, employing instruments known for their standardization, validity, and reliability. The findings informed that teachers possess a low MKT but a high PCK attitude. Thus, they performed the MKT test poorly, as the average score was below 50%. However, teachers were found to have better content knowledge than other MKT constructs and performed well in the pattern function and algebra more than in other areas of mathematics. Teachers demonstrated a highly positive attitude towards integrating PCK in teaching mathematics. Such a positive attitude was inferred from the pedagogical training offered by implementing a competence-based curriculum. Therefore, teachers need to improve their MKT performance, and more research is needed on other teachers apart from TTCs.